The impact of emotions on visual working memory - Teo, Van Chin Hou (2015)
This study examined the impact of emotions on visual working memory. 40 participants (20 males and 20 females), between the ages of 18 to 25, were recruited. The study was conducting using Eprime (Psychology Software Tools, Pittsburgh, PA). The participants were either shown negative images or neutral images from then International Affective Picture Systems (IAPS), they completed a change detection task similar to Brady et al. (2009). In the change detection task, they were shown images of daily objects displayed in a 3 by 2 matrix array, followed by a blank screen, then the single item test array; they had to determine if there were any changes. Mood manipulation was successful as there were statistical differences in pleasant-unpleasant scores between control group (Mdn = 7.00) and negative stimulus group (Mdn= 3.00), U = 1.00, z = - 5.47, p = 0.00< 0.05. However, negative emotions did not affect visual working memory performance, as there were no statistical differences in response accuracy, F (1, 29) = 0.49 < 1, p = 0.49 and reaction time, F (1, 29) = 2.30, p = 0.14. Lastly, there were also no gender differences observed for both response accuracy, F (1, 29) = 0.38 < 1, p = 0.54 and reaction times, F (1, 29) = 1.06, p = 0.31. Even though the results did not support the initial hypotheses, it still has potential implications for future research, in terms of using a new method of mood manipulation and more visual working memory measures.